A Goy Who Speaks Yiddish : Christians and the Jewish Language in Early Modern Germany. - Elyada, Aya. (Palo Alto : Stanford University Press, 2012)
This book explores the unique phenomenon of Christian engagement with Yiddish language and literature from the beginning of the sixteenth century to the late eighteenth century. By exploring the motivations for Christian interest in Yiddish, and the differing ways in which Yiddish was discussed and treated in Christian texts, A Goy Who Speaks Yiddish addresses a wide array of issues, most notably Christian Hebraism, Protestant theology, early modern Yiddish culture, and the social and cultural history of language in early modern Europe. Elyada's analysis of a wide range of philological and theo.
Yiddish in the service of Christian theology. Introduction : Christian Hebraism and the study of Yiddish in early modern Europe -- Yiddish in the Judenmission -- "From the Jews' own books" : Yiddish literature, Christian readers -- Blasphemy, curses, and insults : Yiddish and the Jews' "hidden transcript" -- Ancilla theologiae : Yiddish as a Hilfsmittel for theological studies -- Conclusion : the study of Yiddish and Christian-Jewish relations in early modern Germany -- Yiddish in the Service of Jewish Deception. Introduction : Yiddish in the socioeconomic sphere -- The merchants' tongue : Yiddish and Jewish commerce -- The thieves' jargon : Yiddish and Jewish criminality -- Conclusion : Yiddish as antilanguage -- The Discourse on Yiddish in Early Modern Germany. Introduction : between Hebrew and German : the depictions of Yiddish in Christian writings -- German of the Jews : linguistic affinity and the politics of differentiation -- Yiddish and German in the Judenmission : the limits of linguistic adaptation -- Christian Hebrew and Jewish Yiddish in early modern Germany -- Conclusion : Yiddish-speaking orientals : language shift and the "Verbesserung der Juden."
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Yiddish language -- Study and teaching -- Germany -- History; Yiddish literature -- Study and teaching -- Germany -- History; Christian literature, German -- History and criticism; Yiddish language in literature; Christianity and other religions -- Judaism; Judaism -- Relations -- Christianity; Christian scholars -- Germany -- History; FOREIGN LANGUAGE STUDY -- Scandinavian Languages (Other); Christian literature, German; Christian scholars; Christianity; Interfaith relations; Judaism; Yiddish language in literature; Yiddish language -- Study and teaching; Yiddish literature -- Study and teaching; Germany; HISTORY / Jewish; Electronic books; Criticism, interpretation, etc; History